Reconstructing justice-based legal protection for mental health patients in Indonesian Clinics - Masithoh, Anny Rosiana; Wahyuningsih, Sri Endah; Bawono, Bambang Tri (Journal of Law Science, 2025)
People with mental disorders are often stereotyped as being involved in criminal acts, especially violence and threats to the safety and security of those around them. This perspective causes people with mental disorders to be feared and shunned, even though they need care and protection. Regional governments are responsible for providing mental health services for their communities and playing a strategic role in managing and preventing mental health issues. In Kudus, there are still displaced people with mental disorders who have not received proper care. The local government can progressively address mental health issues through regulatory instruments to ensure that people with mental disorders receive the appropriate treatment and support they need. This study aims to examine the mental health policies of the Kudus local government, emphasizing policies prioritizing human rights. The research uses a normative juridical method involving a thorough analysis of policies concerning people with mental disorders in the Kudus district. The results show that although the Kudus Regional Government has established policies related to mental Disability and mental health, these policies do not sufficiently address the prevention of mental disabilities or fully incorporate human rights considerations.